Dynamic characterization of a masonry arch bridge - Cristina Costa (2005)
The present work addresses the identification of the most relevant dynamic parameters of a stone masonry arch bridge for validation of the numerical model used in the structural analysis. In situ dynamic tests were performed to measure the structural response under ambient vibration in order to characterize the structural dynamic behaviour. Appropriate software was adopted for signal analysis and processing based in the Peak Picking technique and in the Frequency Domain Decomposition.